2018
DOI: 10.1002/cmdc.201700755
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibitors against Newcastle Disease Virus Hemagglutinin‐Neuraminidase

Abstract: Neuraminidase activity is essential for the infection and propagation of paramyxoviruses, including human parainfluenza viruses (hPIVs) and the Newcastle disease virus (NDV). Thus, many inhibitors have been developed based on the 2-deoxy-2,3-didehydro-d-N-acetylneuraminic acid inhibitor (DANA) backbone. Along this line, herein we report a series of neuraminidase inhibitors, having C4 (p-toluenesulfonamido and azido substituents) and C5 (N-perfluorinated chains) modifications to the DANA backbone, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…Indeed, differently to the well-established oxazoline chemistry, 18 it was reported that the acidic treatment of the oxazoline 3a afforded the 4-epi hydroxyl derivative 4b, as a single product, in variable yields (42-88%), calling for further studies. 6,[9][10][11][12][13] As a result of our continuing interest in the sialic acid chemistry/ biochemistry, 2,3,7,[14][15][16][19][20][21][22][23] in this work we solved this mechanistic puzzle, as we unveil that, the acidic hydrolysis of the 4,5-oxazoline 3a affords the amino ester 5, which could be isolated in good yields and fully characterized under appropriate work-up conditions. Furthermore, we detailed the shortened synthesis of the precursor of BCX 2798 (2c) and other sialidase inhibitors (such as BCX 2755 and various C4 triazole derivatives) further highlighting the synthetic utility of 5.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…Indeed, differently to the well-established oxazoline chemistry, 18 it was reported that the acidic treatment of the oxazoline 3a afforded the 4-epi hydroxyl derivative 4b, as a single product, in variable yields (42-88%), calling for further studies. 6,[9][10][11][12][13] As a result of our continuing interest in the sialic acid chemistry/ biochemistry, 2,3,7,[14][15][16][19][20][21][22][23] in this work we solved this mechanistic puzzle, as we unveil that, the acidic hydrolysis of the 4,5-oxazoline 3a affords the amino ester 5, which could be isolated in good yields and fully characterized under appropriate work-up conditions. Furthermore, we detailed the shortened synthesis of the precursor of BCX 2798 (2c) and other sialidase inhibitors (such as BCX 2755 and various C4 triazole derivatives) further highlighting the synthetic utility of 5.…”
mentioning
confidence: 92%
“…As a result of our continuing interest in the sialic acid chemistry/biochemistry, 2,3,7,14–16,19–23 in this work we solved this mechanistic puzzle, as we unveil that, the acidic hydrolysis of the 4,5-oxazoline 3a affords the amino ester 5, which could be isolated in good yields and fully characterized under appropriate work-up conditions. Furthermore, we detailed the shortened synthesis of the precursor of BCX 2798 (2c) and other sialidase inhibitors (such as BCX 2755 and various C4 triazole derivatives) further highlighting the synthetic utility of 5.…”
mentioning
confidence: 98%
See 3 more Smart Citations